2018
DOI: 10.1620/tjem.244.123
|View full text |Cite
|
Sign up to set email alerts
|

Lower Plasma Levels of IL-35 in Patients with Primary Biliary Cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is an autoimmune liver disease. Its histological characteristics, such as progressive intrahepatic bile duct destruction, cholestasis, and liver cirrhosis, are caused by the body's autoimmune disorders. Interleukin (IL)-35 has two subunits (p35 and Ebi3) and is a member of the IL-12 family of heterodimeric cytokines. IL-35 has immunosuppressive functions and plays an important role in many autoimmune diseases. In this study, we compared plasma levels of IL-35 and relative mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Meanwhile, at different stages of disease, IL-35 was positively correlated with the TGF-β closely, which was related to Treg expression level in LC patients. Interestingly, the change trend of the expression levels of TGF-β and IL-35 in serum was consistent with Th17 Tregs in PBC (Li et al, 2018). Studies shown that the expression level of IL-35 might have relevance to histological grade and the severity of PBC.…”
Section: Interleukin-35 and Liver Cirrhosissupporting
confidence: 65%
See 2 more Smart Citations
“…Meanwhile, at different stages of disease, IL-35 was positively correlated with the TGF-β closely, which was related to Treg expression level in LC patients. Interestingly, the change trend of the expression levels of TGF-β and IL-35 in serum was consistent with Th17 Tregs in PBC (Li et al, 2018). Studies shown that the expression level of IL-35 might have relevance to histological grade and the severity of PBC.…”
Section: Interleukin-35 and Liver Cirrhosissupporting
confidence: 65%
“…The expression level of IL-35 in serum in PBC patients was lower than that in healthy individuals. The expression level of Ebi3 mRNA was decreased in PBC patients as well, but no statistical difference in the expression level of p35 mRNA level (Li et al, 2018). IL-35 in PBC patients was inversely associated with expression levels of clinical parameters, such as ALP, GGT, AST, ALT, and cytokines produced by CD4+ T cells (IFN-γ, IL-23, IL-17).…”
Section: Interleukin-35 and Liver Cirrhosismentioning
confidence: 85%
See 1 more Smart Citation
“…We found that the levels of IL-6, IL-8, and TNF-α in the patients were higher than that in HC (Mann-Whitney test Z = −6.997, P < 0.001; Z = −7.180, P < 0.001; Z = −6.599, P < 0.001, respectively) (Figures 1A–C). Moreover, as Li et al (22) proposed, the serum abnormal cytokines levels may have a linear relationship with the parameters for liver functions (AKP, γ-GT, and TBiL) in PBC patients. As expected, the results from the present study showed that there were a positive correlations between the levels of AKP and IL-6 ( r = 0.430, p = 0.004), IL-8 ( r = 0.389, p = 0.010) and TNF-α ( r = 0.496, p = 0.001) (Figures 1D–F).…”
Section: Resultsmentioning
confidence: 96%
“…Patients with PBC exhibit a marked increase in the frequency and absolute number of blood and liver NK cells. The increased presence of scattered NK cells near disrupted small bile ducts was observed at an increased frequency in liver tissues from PBC patients by immunohistochemical observation [ 2 ]. A similar phenomenon was observed in our animal model.…”
Section: Discussionmentioning
confidence: 99%